Fantasy Soccer and Mathematics - Flockhart, Dan (Jossey-Bass, 2007)
This workbook is designed to be used in conjunction with Fantasy Soccer and Mathematics: A Resource Guide for Teachers and Parents. The games and activities in Fantasy Soccer and Mathematics were created to get you excited about learning and practicing math, even if you are not a big sports fan